Au–Ag nanoalloy molecule-like clusters for enhanced quantum efficiency emission of Er3+ ions in silica. Issue 42 (29th April 2015) - Cesca, Tiziana; Kalinic, Boris; Michieli, Niccolò; Maurizio, Chiara; Trapananti, Angela; Scian, Carlo; Battaglin, Giancarlo; Mazzoldi, Paolo; Mattei, Giovanni
Abstract : (Au–Ag) N nanoalloy clusters made up of N = 10–15 atoms increase by an order of magnitude the room temperature photoemission intensity of Er 3+ in silica, better than monometallic Au N clusters of the same size. Abstract : The occurrence of a very efficient non-resonant energy transfer process forming ultrasmall Au–Ag nanoalloy clusters and Er 3+ ions is investigated in silica. The enhancement of the room temperature Er 3+ emission efficiency by an order of magnitude is achieved by coupling rare-earth ions to molecule-like (Au x Ag1− x ) N alloy nanoclusters with N = 10–15 atoms and x = 0.6 obtained by optimized sequential ion implantation on Er-implanted silica. For comparison, Au N nanoclusters obtained by the same approach and with the same size and numerical density showed an enhancement by only a factor of 2 with respect to pure Er emission, demonstrating the beneficial effect of using nanoalloyed clusters. The temperature evolution of the energy transfer process is investigated by photoluminescence and exhibits a maximum efficiency at about 600 °C, where the clusters reach the optimal size and the silica matrix completely recovers the implantation damage. The nanoalloy cluster composition and size have been studied by EXAFS analysis, which indicated a stronger Ag–O interaction with respect to the Au–O one and a preferential location of the Ag atoms at the nanoalloy cluster surface.